Factors that affecting adoption of cashless payment in Malaysia night market - Li, Fanny Jia Jia (2022)
The research aimed to investigate the factors that affecting adoption of cashless payment in Malaysia night market. The independent variables for this research are perceived usefulness, perceived ease of use, perceived security, relative advantage, and social influence. The dependent variables for this research were adoption of cashless payment. The focus of this research was Malaysia night market. UTAUT, TAM and ECT were adopted in this research. The targeted respondents for this research were the users of cashless payment in Malaysia night market. Cronbach Alpha, Spearman’s Correlation Analysis and Multiple Regression Analysis were conducted in this research. The outcome of the research showed that perceived security and social influence were insignificant towards the adoption of cashless payment. Some limitations and suggestions are included in the study to provide a better idea for future researchers and the service provider to enhance the adoption of cashless payment in Malaysia.